Engineering Catalytic CoSe–ZnSe Heterojunctions Anchored on Graphene Aerogels for Bidirectional Sulfur Conversion Reactions. Issue 1 (27th October 2021) - Ye, Zhengqing; Jiang, Ying; Yang, Tianyu; Li, Li; Wu, Feng; Chen, Renjie
Abstract: Sluggish sulfur reduction and lithium sulfide (Li2 S) oxidation prevent the widespread use of lithium–sulfur (Li–S) batteries, which are attractive alternatives to Li−ion batteries. The authors propose that a transition metal selenide heterojunction (CoSe–ZnSe) catalytically accelerates bidirectional sulfur conversion reactions. A combination of synchrotron X‐ray absorption spectroscopy and density functional theory calculations show that a highly active heterointerface with charge redistribution and structure distortion effectively immobilizes sulfur species, facilitates Li ion diffusion, and decreases the sulfur reduction and Li2 S oxidation energy barriers. The CoSe–ZnSe catalytic cathode exhibits high areal capacities, good rate capability, and superior cycling stability with capacity fading rate of 0.027% per cycle over 1700 cycles. Furthermore, CoSe–ZnSe heterojunctions anchored on graphene aerogels (CoSe–ZnSe@G) enhance ionic transport and catalytic activity under high sulfur loading and lean electrolyte conditions. A high areal capacity of 8.0 mAh cm −2 is achieved at an electrolyte/sulfur ratio of 3 µL mg −1 . This study demonstrates the importance of bidirectional catalytic heterojunctions and structure engineering in boosting Li–S battery performances. Abstract : A highly active transition metal selenide heterojunction (CoSe–ZnSe) is presented as a bidirectional catalyst for lithium–sulfur batteries. The improved trapping–diffusion–conversion for polysulfides redox afforded by the charge redistributed heterointerface is demonstrated by synchrotron X‐ray absorption spectroscopies and first‐principles calculations. Furthermore, CoSe–ZnSe heterojunctions anchored on graphene aerogels are designed to maximize the catalytic conversion of polysulfides under lean‐electrolyte operation.